Political Parties and Churches in Argentina: Intersections in Quicksand - Carbonelli, Marcos Andres (2018)
This work intends to analyze the historical intersections between political parties and churches in Argentina, focusing on Catholic and evangelical interventions, since these are the religious organizations with the most presence, interests and connections in this space. Our analysis will be based on a binary classification: the term direct intersections refers to the decision by religious agents to form their own party structures, while indirect intersections is the denomination for those practices through which churches exert their influence on political parties without getting involved in the electoral arena. After establishing the degree of effectiveness of these different strategies, we will discuss their impact in the context of the consolidation of democracy in present-day Argentina. Methodologically, the analysis relies on a comprehensive and critical review of the scientific production about religion and politics in the country being studied.